Fekete-Szego problem of certain class of univalent functions / Hoo Siew Lee Hoo Lew Aun, Siti Nor Asiah Muhamad Atan and Nur Alysha Dania Roslan - Hoo Lew Aun, Hoo Siew Lee; Muhamad Atan, Siti Nor Asiah; Roslan, Nur Alysha Dania (2023)
The Fekete-Szego problem is a classical problem in complex analysis that concerns the properties of univalent functions. Specifically, there is limited method to find geometric properties of certain class of univalent function. This study is conducted to define new class of univalent functions and to find upper bound of Fekete-Szego problem for this class of functions using Hankel determinant.